Effects of pH and Salts on Physical and Mechanical Properties of Pea Starch Films. Issue 7 (31st May 2016) - Choi, W.S.; Patel, D.; Han, J.H.
Abstract: To identify the significant contribution of intermolecular hydrogen bonds of starch molecules to the film structure formation, pH of film‐forming solutions was adjusted and also various salts (NaCl, CaCl2, CaSO4, and K2 SO4 ) were mixed into the glycerol‐plasticized pea starch film. The film made from pH 7 possessed the highest tensile strength‐at‐break (2 times) and elastic modulus (4 to 15 times) and the lowest elongation‐at‐break compared with those of the films made from acid and alkali environments. The pH 7 film also has the highest film density and the lowest total soluble matter. At the level of 0.01 to 0.1 M of CaSO4 and 0.1 M of K2 SO4 in a kilogram of starch, the water solubility of the film increased, while chloride salts slightly lowered the solubility. NaCl and CaSO4 reduced water vapor permeability (WVP), while CaCl2 slightly increased WVP at 0.01 and 0.06 M concentrations, and K2 SO4 significantly increased WVP at 0.03 and 0.15 M. Presence of salts increased tensile strength (5 to 14 times than the control films) and elastic modulus (35 to 180 times) of starch film at 0.01 to 0.03 M of CaSO4 and K2 SO4 . Elongation‐at‐break increased significantly as salt concentration increases to an optimal level. However, when the concentration exceeded above the optimal level, the E of starch films decreased and showed no significant difference from the control film. Overall, the addition of salts modified physical and mechanical properties of pea starch films more than pH adjustment without any salt addition.